Underwater Light Manipulation by the Benthic Diatom Ctenophora pulchella: From PAR Efficient Collection to UVR Screening - Edoardo De Tommasi (MDPI AG, 2021)
Several species of diatoms, unicellular microalgae which constitute the main component of phytoplankton, are characterized by an impressive photosynthetic efficiency while presenting a noticeable tolerance versus exposure to detrimental UV radiation (UVR). In particular, the growth rate of the araphid diatom Ctenophora pulchella is not significantly affected by harsh treatments with UVR, even in absence of detectable, specific UV-absorbing pigments and even if it is not able to avoid high UV exposure by motility. In this work we applied a multi-disciplinary approach involving numerical computation, photonics, and biological parameters in order to investigate the possible role of the frustule, micro- and nano-patterned silica shell which encloses the cell, in the ability of C. pulchella to efficiently collect photosynthetic active radiation (PAR) and to simultaneously screen the protoplasm from UVR. The characterization of the photonic properties of the frustule has been accompanied by in vivo experiments conducted in water in order to investigate its function as optical coupler between light and plastids.